(untitled) (Baghdad Science Journal, 2025)
The glycated haemoglobin A1c(HbA1c) and Fasting blood glucose(FBG) effect on type1 diabetic pateints as a screening tests and as a gold standard for assessing glycemic control in subjects with diabetes were studied . Ninety one blood samples were collected in a peroid between June and the end of November 2012 at AL- Kindy Diabetic Center and Central Child Hospital,48 Females and 43 Males , aging between (11 month- 18 year), are divided into three groups, newly diagnosed , ongoing and healthy control group, with duration of disease between(1 day-3months) and (from birth-8 years) for newly diagnosed and ongoing groups respectevily . The results showed that FBG and HbA1c for newly diagnosed were high (291 mmol/l and 10.6%) respectevily with short duration mean (3.32 week) while ongoing group (207mmol/L and 7.4%) with duration mean(154.5 week) compared with control group values (92.6mmol/L and 4.9%).There was a significant differences between FBG in patients and control at P value < 0.005, and p < 0.05 between HbA1c for patients and control .The correlation of FBG in patients and duration of disease were ( r= - ve 0.19) and for the control group ( r= -ve 0.49 ).When we compared FBG and HbA1c in patient the correlation was (+ve 0.64) .This study concluds that the combined use of FBG and HbA1c are very important for assessing glycemic control and enhanced the detection of diabetes individuals at high risk for diabetes.